IMPLEMENTATION OF DESIGN THINKING IN THE BRAND ACTIVATION PROCESS OF BAGUS KUMBAH MSME (SHOE CARE SERVICE BUSINESS) - Desthyo Putra Pangestu; Didit Widiatmoko Soewardikoen (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2026)
Shoe fashion trends are increasingly influenced by various needs, such as functional, collection, or resale. This trend opens up business opportunities for shoe care services, as not all members of the general public can carry out appropriate shoe care, because it requires special knowledge and expertise. However, there are obstacles in introducing shoe care service brands to the public, as experienced by the Bagus Kumbah brand, one of the shoe washing service brands that is relatively new. In the initial stage, business improvement efforts were mapped on the business model canvas after identifying various problems, such as the need to increase public awareness of the brand.Efforts to reach and determine consumer targets to expand the scope of consumer targets and establish treatment processes for interaction with consumers directly and indirectly through social media to provide an impression of experience during the transaction process through various design solutions produced. The problem-solving process usesdesign thinking, which includes the process of data acquisition, data processing, generating various problem solutions, and implementing the initial solution. As a result, a series of brand activation processes has an impact on increasing the number of engagements on Bagus Kumbah's social media, increasing the number of new consumers,and further increasing the loyalty of existing consumers.meningkatkan loyalitas konsumen lama.